Post-inflammatory Polyp Burden as a Prognostic Marker of Disease-outcome in Patients with Inflammatory Bowel Disease. (2nd November 2022) - Ellul, Pierre; Schembri, John; Vella Baldacchino, Andrea; Molnár, Tamas; Resal, Tamas; Allocca, Mariangela; Furfaro, Federica; Buono, Arianna Dal; Theodoropoulou, Angeliki; Fragaki, Maria; Tsoukali, Emmanouela; Mantzaris, Gerassimos J; et al.
Abstract: Background and Aims: Post-inflammatory polyps [PIPs] are considered as indicators of previous episodes of severe inflammation and mucosal ulceration. Inflammatory bowel disease [IBD], namely Crohn's disease [CD] and ulcerative colitis [UC], exhibit a perpetuating, relapsing and remitting pattern, and PIPs are a frequent sequela of chronicity. The aim of this study was to determine whether a high PIP burden is associated with a more severe disease course in patients with IBD. Methods: This was a multinational, multicentre, retrospective study. IBD patients previously diagnosed with PIPs were retrieved from the endoscopic database of each centre. PIP burden was evaluated and associated with demographic and clinical data as well as factors indicating a more unfavourable disease course. Results: A total of 504 IBD patients with PIPs were recruited [male: 61.9%]. The mean age at IBD diagnosis was 36.9 [±16.8] years. Most patients [74.8%] were diagnosed with UC. A high PIP burden was present in 53.4% of patients. On multivariable Cox regression analysis, a high PIP burden was independently associated with treatment escalation (hazard ratio [HR] 1.35, 95% confidence interval [CI] 1.04–1.75; p = 0.024), hospitalization [HR 1.90; 95% CI 1.24–2.90; p = 0.003], need for surgery [HR 2.28; 95% CI 1.17–4.44, p = 0.02] and younger age at diagnosis [HR 0.99, 95% CI 0.98–0.99; p = 0.003]. Conclusion: PIP burden was associated with a more severe outcome. Future prospective studies should focus on the characterization of PIP burden as to further risk stratify this patient cohort.